Socio-cultural Factors Influencing the Incidence of Tuberculosis in Abuja-Leather Mining Camp, Oyo State, Nigeria (2016)
Tuberculosis (TB) is a global pandemic with Nigeria ranked among countries with a high burden of the disease. While some countries have succeeded in halving the prevalence rate, the situation is not the same for Nigeria. This study utilized a semistructured questionnaire administered on 394 randomly selected respondents. Twelve In-depth Interviews (IDIs) and four Key Informant Interviews (KIIs) were conducted. Respondents’ mean age was 35.0±10.4 years. Over 90.0% had heard of TB, while over 60.0% identified cough that last longer than 3 weeks and coughing out blood as symptoms of TB. Respondents acquired their knowledge of TB from radio, health workers, family, friends and colleagues. While there was poor knowledge of other symptoms of TB, less than half of the respondents had knowledge of how TB could be cured and prevented. More than half of the respondents identified smokers and alcoholics as people that can be infected with TB. Regression analysis showed that only sex, level of education and ethnicity had significant independent prediction on the knowledge of how TB is contracted (R=.329, R2=.108, F=5.551, P<.05). More than half of the respondents had a belief that tuberculosis is a punishment from gods/goddess, a hereditary disease, and a spiritual attack from the enemies. Study showed that smoking, talking, coughing and sneezing while working in group in the mining pits especially with an infected person increase TB spread. The study recommends public health education and enlightenment programmes to reduce the spread of TB in relevant communities.